Advances in XML Information Retrieval Third International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2004, Dagstuhl Castle, Germany, December 6-8, 2004 - Fuhr, Norbert; Lalmas, Mounia; Malik, Saadia; Szlávik, Zoltán (Information Systems and Applications, incl. Internet/Web, and HCI, 2005)
The ultimate goal of many information access systems (e.g., digital libraries, the Web, intranets) is to provide the right content to their end-users. This content is increasingly a mixture of text, multimedia, and metadata, and is formatted according to the adopted -W3C standard for information repositories, the so-called eXtensible Markup L- guage (XML). Whereas many of today's information access systems still treat do- ments as single large (text) blocks, XML offers the opportunity to exploit the internal structure of documents in order to allow for more precise access thus providing more specific answers to user requests. Providing effective access to XML-based content is therefore a key issue for the success of these systems. The aim of the INEX campaign (Initiative for the Evaluation of XML Retrieval), which was set up at the beginning of 2002, is to establish infrastructures, XML test suites, and appropriate measurements for evaluating the performance of information retrieval systems that aim at giving effective access to XML content. More precisely, the goal of the INEX initiative is to provide means, in the form of a large XML test collection and appropriate scoring methods, for the evaluation of content-oriented XML retrieval systems.